A new genus of the mantispid-like Paraberothinae (Neuroptera: Berothidae) from Burmese amber, with special consideration of its probasitarsus spine-like setation - Makarkin, Vladimir N. (Zootaxa, 2015)
Creagroparaberotha groehni gen. et sp. nov. (Neuroptera: Berothidae: Paraberothinae) is described from the earliest Cenomanian Burmese amber. The revised diagnosis of Paraberothinae is provided. The specialized probasitarsi in Paraberothinae, Rhachiberothinae (Berothidae) and Symphrasinae (Mantispidae) are considered as a homoiology (parallelism), i.e., convergent modifications of a homologous structure. The genus Berothone Khramov, 2015 is considered to belong to the subfamily Mesithoninae (Berothidae).